Safety and Regulation of Fat Grafting - Raj, Sarth; Abu-Ghname, Amjed; Davis, Matthew J.; Izaddoost, Shayan A.; Winocour, Sebastian J. (Seminars in Plastic Surgery, 2020)
Today, fat grafting has wide applicability across plastic surgery disciplines, including both aesthetic and reconstructive procedures. However, much controversy has surrounded adipose tissue transfer throughout the 20th century, necessitating extensive research to improve the fat grafting process and to better understand its associated complications and benefits. Initial concerns included the technical difficulties of properly handling and processing adipose to ensure adequate outcomes. As these issues were addressed, more modern concerns were raised by the U.S Food and Drug Administration and the general scientific community regarding the oncological potential of adipose tissue and its potential interference with breast cancer screenings. Today, many formalized clinical studies have evidenced the safety of fat grafting, allowing the procedure to gain widespread popularity and opening avenues for future applications.
Keywords: fat grafting; autologous adipose tissue transfer; safety; regulations